Advanced analytical methods for preventing scaling and ensuring water quality in bioenergy generation processes - Souza, Érik Geraldo da Silva [UNESP] (2025)
This study addresses the challenges associated with bioelectricity generation in the sugar-energy industry, focusing on scaling formation and water quality management in the steam generation process. Utilizing water-tube boilers fueled by sugarcane bagasse and straw, these biorefineries produce high-pressure steam to drive turbines and generate electricity for both internal consumption and the national power grid. The thesis is structured into two chapters. The first chapter investigates scaling formation in turbogenerators, employing techniques such as energy-dispersive X-ray fluorescence (ED-XRF) and principal component analysis (PCA). Samples collected from critical points in the turbines and boilers revealed the predominant presence of elements such as silicon (Si), sulfur (S), chlorine (Cl), potassium (K), and calcium (Ca), which contribute to scaling formation. The results emphasize the direct relationship between water quality and scaling, highlighting the importance of rigorous water treatment controls to prevent impacts on equipment efficiency. The second chapter evaluates the quality of boiler feedwater using exploratory methods such as PCA and minimum spanning tree (MST)-based clustering. The analysis of 120 water and steam samples identified patterns and levels of purity, with critical variables including conductivity, SiO₂ content, and pH. These approaches eliminated subjective biases and provided precise information to optimize water management practices in sugarcane biorefineries. The integrated results demonstrate the complementarity of the applied methods, offering a robust foundation for preventive monitoring and cogeneration process optimization. This study contributes to preserving critical equipment, reducing operational costs, and promoting sustainability in industries that use biomass as an energy source.